Identification of next-generation International Humic Substances Society reference materials for advancing the understanding of the role of natural organic matter in the Anthropocene - Yu-Ping Chin; Diane M. McKnight; Juliana D’Andrilli; Nicole Brooks; Kaelin Cawley; Jennifer Guerard; E. Michael Perdue; Colin A. Stedmon; Paul G. Tratnyek; Paul Westerhoff; Andrew S. Wozniak; Paul R. Bloom; et al. (Aquatic Sciences, 2023)
Many challenges remain before we can fully understand the multifaceted role that natural organic matter (NOM) plays in soil and aquatic systems. These challenges remain despite the considerable progress that has been made in understanding NOM’s properties and reactivity using the latest analytical techniques. For nearly 4 decades, the International Humic Substances Society (IHSS, which is a non-profit scientific society) has distributed standard substances that adhere to strict isolation protocols and reference materials that are collected in bulk and originate from clearly defined sites. These NOM standard and reference samples offer relatively uniform materials for designing experiments and developing new analytical methods. The protocols for isolating NOM, and humic and fulvic acid fractions of NOM utilize well-established preparative scale column chromatography and reverse osmosis methods. These standard and reference NOM samples are used by the international scientific community to study NOM across a range of disciplines from engineered to natural systems, thereby seeding the transfer of knowledge across research fields. Recently, powerful new analytical techniques used to characterize NOM have revealed complexities in its composition that transcend the “microbial” vs. “terrestrial” precursor paradigm. To continue to advance NOM research in the Anthropocene epoch, a workshop was convened to identify potential new sites for NOM samples that would encompass a range of sources and precursor materials and would be relevant for studying NOM’s role in mediating environmental and biogeochemical processes. We anticipate that expanding the portfolio of IHSS reference and standard NOM samples available to the research community will enable this diverse group of scientists and engineers to better understand the role that NOM plays globally under the influence of anthropogenic mediated changes.